Right hemisphere dominance for language in a woman with schizophrenia and a porencephalic cyst of the left hemisphere. Issue 3 (3rd May 2016) - de Oliveira-Souza, Ricardo; Monteiro, Myriam; Pacheco, Paula; Tovar-Moll, Fernanda; Mattos, Paulo; Moll, Jorge; Nazar, Bruno Palazzo
ABSTRACT: A large left hemisphere porencephalic cyst was incidentally found in a 48-year-old woman (MS) with a Diagnostic and Statistical Manual (DSM)-5 diagnosis of schizophrenia. The encephaloclastic characteristics of the cyst indicated that it was acquired between the 22nd and 24th gestational weeks, after the major waves of neuronal migration had tapered off. The cyst destroyed the left temporal and occipital lobes, and the inferior parietal lobule. Surprisingly, MS had no evidence of aphasia, alexia, agraphia, or ideational apraxia; in contrast, cognitive functions dependent on the integrity of the right hemisphere were severely impaired. To test the hypothesis that the development of language in MS took place at the expense of functions that are normally carried out by the right hemisphere, we investigated MS's correlates of oral comprehension with fMRI as a proxy for auditory comprehension and other cognitive functions strongly lateralized to the posterior left hemisphere, such as ideational praxis and reading. Comprehension of spoken language engaged the homologous of Wernicke's area in the right planum temporale . Porencephaly may represent a natural model of neuroplasticity supervening at predictable epochs of prenatal development.